Dominant finance and Stagnant economics - "Sen, Sunanda" (New Delhi, 2014)
The volume traces the evolution of global finance over the last half century and contextualizes the heightened uncertainty on account of speculation in deregulated markets along with crisis and recession in the real economy.
Keywords: "Financial crisis, International finance"